Filsafat Behaviorisme Dalam PAUD Perspektif Rudolf Steiner - Zahratur Rahma; Maemonah Maemonah (UIN Sultan Maulana Hasanudin Banten, 2021)
This article aims to understand the philosophy of Behaviorism in early childhood education from the perspective of Waldorf (Rudolf Steiner) which is applied to its usefulness in the learning process. Steiner is an educational theory commonly referred to as Waldorf, the word